2015
DOI: 10.1155/2015/327287
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Hallmarks Promising Accuracy for the Diagnosis of Various Carcinomas: Results from a Meta-Analysis

Abstract: Background. Recent studies have shown that microRNAs (miRNAs) have diagnostic values in various cancers. This meta-analysis seeks to summarize the global diagnostic role of miR-155 in patients with a variety of carcinomas. Methods. Eligible studies were retrieved by searching the online databases, and the bivariate meta-analysis model was employed to generate the summary receiver operator characteristic (SROC) curve. Results. A total of 17 studies dealing with various carcinomas were finally included. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Its expression in macrophages increases in response to LPS, TNF-α, and IFN-β [ 86 ]. Its serum levels have a diagnostic role in patients with a variety of carcinomas [ 87 ]. MiR-155 upregulation has been described in bone marrow-derived dendritic cells (BMDCs) under activating conditions [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its expression in macrophages increases in response to LPS, TNF-α, and IFN-β [ 86 ]. Its serum levels have a diagnostic role in patients with a variety of carcinomas [ 87 ]. MiR-155 upregulation has been described in bone marrow-derived dendritic cells (BMDCs) under activating conditions [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…They bind to the 3′ untranslated region (UTR) of their target mRNAs, modulating mRNA stability and/or translation [ 4 6 ]. Up to now, many miRNAs have been reported to be related to various cancer carcinogenesis and progression including breast cancer [ 7 11 ]. It has been confirmed that miR-340 are differentially expressed between BC patients with metastasis versus these without metastasis and miR-340 are implicated in the status of BRCA1/2 in BC patients [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 53 Apart from that, Wu et al revealed that miR-155 is likely to be used in a variety of cancer screening tests, with a pooled sensitivity of 0.76 and specificity of 0.82. 54 …”
Section: Discussionmentioning
confidence: 99%